Studi Pengolahan Air Limbah dalam Menurunkan Kadar BOD dan COD di Pelabuhan Perikanan Samudra Kendari - Ranno Marlany Rachman; Romy Talanipa; Abdul Rahim Sya’ban (Prosiding ESEC, 2022)
Wastewater is polluted used water resulting from human activities and activities. Wastewater entering the Wastewater Treatment Installation System (WWTP) is treated before being channeled into public drainage. This study aimed to determine the wastewater treatment system using aeration, sedimentation, and oxidation methods to reduce BOD and COD levels of WWTP in PPS Kendari. This research is a quantitative descriptive that is to determine the performance of each wastewater treatment plant by comparing the test results of water samples before and after treatment from aeration tanks, sedimentation tanks to oxidation tanks. Before entering the treatment process, the initial wastewater sample testing results had a BOD value of 112.6 mg/L and a COD value of 260 mg/L. The results of the research on the performance of the aeration basin treatment can reduce BOD levels by 22.58% and COD levels by 28%, wastewater treatment with the sedimentation method can reduce BOD levels by 21.31% and COD levels by 36.19%, in water treatment waste with oxidation method can reduce BOD levels by 23.83% and COD levels by 35.79%, wastewater treatment plants using aeration, sedimentation and oxidation methods can reduce BOD levels by 53.59% (52.25 mg/L) and COD of 70.5% (76.7 mg/L). These results have met the wastewater quality standard of Ministerial Regulation No. 6 of 2007.